HISTORY AND PROSPECTS OF DEVELOPMENT OF RURAL INFRASTRUCTURE IN SAMARKAND REGION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article discusses the history of rural infrastructure development in Samarkand region, the construction of schools, vocational colleges, hospitals in rural areas and the construction of modern housing in rural areas, the development of services to the rural population.